Effects of Daily Consumption of Soy Products on Basic/Instrumental Activities of Daily Living in Community-Dwelling Japanese Women Aged 75 Years and Older: A 4-Year Cohort Study - Narumi Kojima; Miji Kim; Kyoko Saito; Yuko Yoshida; Hirohiko Hirano; Shuichi Obuchi; Hiroyuki Shimada; Takao Suzuki; Hajime Iwasa; Hunkyung Kim (Mary Ann Liebert, 2023)
Introduction: Since soy isoflavones compensate for age-related estrogen reduction, adequate intake of soy products may prevent the decline in activities of daily living (ADL) due to estrogen reduction in women. However, it is unclear whether regular soy product intake prevents ADL decline. This study examined the effects of soy product consumption on basic/instrumental ADL (BADL/IADL) in Japanese women 75 years or older for 4 years. Materials and Methods: The subject population consisted of 1289 women aged 75 years or older living in Tokyo who underwent private health examinations in 2008. For 1114 (or 1042) participants without baseline BADL (or IADL) disability, we examined the association between baseline soy product consumption frequency and the BADL (or IADL) disabilities 4 years later using logistic regression analyses. The models were adjusted for baseline age, or further for dietary variety for food groups other than soy products, exercise and sport participation, smoking, pre-existing disease number, and body mass index. Results: Regardless of adjustment for potential confounding factors, less frequent soy product consumption was associated with higher BADL or IADL disability incidence. In the fully adjusted models, the trend toward a higher incidence of disabilities with less frequent soy product consumption was statistically significant for both BADL (p?=?0.001) and IADL (p?=?0.007). Conclusions: Those who consumed soy products more frequently at baseline were less likely to develop BADL and IADL disabilities after 4 years than those who did not. The results show that daily soy product consumption may prevent functional ADL decline in older Japanese women.